Relationship Between Exclusive Breastfeeding Status and Nutritional Status of Infants Aged 7-12 Months - Novi Kusumaningtyas; Jenie Palupi; Eni Subiastutik; Lulut Sasmito (Universitas Nurul Jadid Paiton Probolinggo, East Java, Indonesia, 67291, 2026)
Malnutrition remains a major public health concern that contributes to infant morbidity and mortality worldwide. One of the important factors associated with infant nutritional status is exclusive breastfeeding, which provides optimal nutrition and may prevent long-term health problems such as stunting. However, previous studies have shown inconsistent findings regarding the relationship between exclusive breastfeeding and infant nutritional status, particularly among infants aged 7–12 months. Therefore, this study aimed to analyze the relationship between exclusive breastfeeding status and the nutritional status of infants aged 7–12 months in the working area of the Kotaanyar Community Health Center, Probolinggo Regency. This study used a correlational analytic design with a cross-sectional approach. The population consisted of 79 infants aged 7–12 months, and 64 respondents were selected using proportional stratified random sampling. Data were analyzed using the Lambda test. The results showed that 53.1% of infants did not receive exclusive breastfeeding, while 62.5% had good nutritional status. Statistical analysis revealed that the p-value was 0.95, which was greater than α = 0.05, indicating that there was no significant relationship between exclusive breastfeeding status and the nutritional status of infants aged 7–12 months. In conclusion, exclusive breastfeeding status was not significantly associated with the nutritional status of infants aged 7–12 months in the Kotaanyar Community Health Center area.